Author Response: International consensus guidance for management of myasthenia gravis: Executive summary. (31st January 2017) - Sanders, Donald B.; Wolfe, Gil I.; Narayanaswami, Pushpa
Abstract : We appreciate the comments of Li et al. on our article. 1 The 2000 Myasthenia Gravis Foundation of America Task Force definition of minimal manifestations included the statement "This class recognizes that some patients who otherwise meet the definition of CSR or PR do have weakness that is only detectable by careful examination." 2 In our article, we noted that "Clinical examination is assumed to have been performed by physicians skilled in the evaluation of neuromuscular disease." 1 Thus, only weakness that is not clinically important would be acceptable under our definition of MMS.